Effects of Acute Exercise Bouts on Cardiovascular Biomarkers in Runners with Exercise-Induced Hypertension - Young-Joo Kim; Han-Soo Park; Sang-Hyun Nam; Sang-Hoon Kim; So-Eun Lee; Jae-Hee Choi; Yong-Bum Park; Jin-Ho Yoon (Sports)
Exercise-induced hypertension (EIH) has increasingly been observed among middle-aged long-distance runners, raising concerns about cardiovascular risk. This study aimed to investigate acute changes in cardiovascular biomarkers associated with vascular inflammation, oxidative stress, antioxidant defense, endothelial function, and myocardial burden in runners with EIH. Thirty-seven middle-aged male runners (aged 40–65 years) were categorized into a normal blood pressure group (NBPG; systolic blood pressure <210 mmHg, n = 23) and an EIH group (EIHG; ≥210 mmHg, n = 14) based on maximal systolic blood pressure during a graded exercise test (GXT). Participants performed a 30 min treadmill run at 80% heart rate reserve, and blood samples were collected before and after exercise. The biomarkers analyzed included high-sensitivity C-reactive protein (hs-CRP), derivatives of reactive oxygen metabolites (d-ROMs), biological antioxidant potential (BAP), nitric oxide (NO), superoxide dismutase (SOD), and N-terminal pro-brain natriuretic peptide (NT-proBNP). The results show that the EIHG exhibited increased NT-proBNP and SOD levels, along with a reduced NO response, indicating elevated myocardial stress and impaired vasodilation. hs-CRP was positively correlated with multiple hemodynamic indices, and SOD levels were associated with maximal systolic pressure and myocardial burden. These findings highlight the need for individualized monitoring and cardiovascular risk management in runners with EIH.